Wordwall as an Interactive Media to Increase Social Studies Learning Motivation - Salwa Dwi Tarishah; Ika Yatri (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2025)
Social Studies (IPS) learning in elementary schools faces significant challenges due to low student motivation, stemming from the theoretical nature of the subject matter and conventional teaching approaches. Observations at SDN Balekambang 03 Pagi reveal minimal student enthusiasm, lack of active participation, and suboptimal learning outcomes in fifth-grade Social Studies classes. This study aims to analyze the effectiveness of implementing the interactive learning media Wordwall in enhancing the motivation to learn Social Studies among fifth-grade students at SDN Balekambang 03 Pagi. The research employs a qualitative approach with a descriptive design. The subjects were 28 students from class VB selected through purposive sampling. Data collection was conducted using method triangulation: participatory observation, in-depth interviews with teachers and students, and documentation of the learning process. Data analysis followed a model of data reduction, data presentation, and conclusion drawing, with source triangulation used for validation. The implementation of Wordwall demonstrated a significant transformation in the dynamics of Social Studies learning. Students showed increased enthusiasm, active participation, and engagement in learning activities. The use of various educational game formats such as interactive quizzes, spin wheels, and matching games successfully shifted students' perceptions of Social Studies from boring to fun and engaging. Teachers reported positive changes in student attitudes, with a reduction in disruptive behavior and an increase in learning focus. This study contributes to the development of innovative Social Studies learning strategies through the integration of digital technology. The findings support the implementation of game-based learning as an effective solution to address motivational issues in primary education. Keywords: Wordwall, learning motivation, Social Studies learning